The Responsibility of Incorrect Nutrition in the Expansion of Bowel Tumors: A Nutritional Survey Study - Amal R. Agila (مجلة البيان العلمية, 2023)
This effort regards as a part of diet-related tumor research. The present work offers a clue of the severity of bowel tumor incidence in Tripoli and Misurata, Libya over the past eleven years to spot the effect of incorrect dietary routines and living ways in expanding bowel tumors. 265 males and 203 females aged (25-85) years were diagnosed with bowel malignancy. Moreover, a nutritional survey study was performed on 100 Libyan patients (51 men and 49 women) from 1 January to 30 June, 2015. Participants were asked to report their dietary customs and living routine one year prior to getting hurt bowel tumors. The data proves that the incidence of bowel tumor is increasing over time from January 2004 to December 2014. Men are almost 13.2 % more likely than women to develop bowel tumor. There was a statistically significant association between males and females for getting bowel tumors (P= 0.039). The disease mostly happens in men >50 years old and in women >30 years old. A nutritional survey study finds that 24% of cases had a family history to develop cancer. Women had a family history to develop tumors than men. Results provide that more than half of patients are likely to drink 1 liter of water per day. Also, men tend to drink more water and consume red meat than women. All patients did not do exercise and had irregular sleeping time and all men were frequent smokers.